Bimbingan Teknis Pajak Daerah dan Retribusi Daerah (PDRD) Kabupaten Puncak, Propinsi Papua Tengah - Marselinus Asri; Bartholomeus Tandiayu; Anthony Holly; Abner Tahendrika (Lembaga Publikasi Ilmiah Nusantara, 2026)
This community service program was a collaboration between the Faculty of Economics and Business, Atma Jaya University Makassar, and the Regional Revenue Agency (Bapenda) of Puncak Regency, Central Papua. The activity was conducted in the form of Technical Guidance on Regional Taxes and Levies (PDRD), held from March 11 to 14, 2025, at Kyriad Haka Hotel, Makassar, South Sulawesi. The main objective was to strengthen the capacity of Bapenda officials in understanding the potential of the Gross Regional Domestic Product (GRDP), mastering regional tax calculation techniques, and mapping local revenue (PAD) opportunities to optimize regional income. Participants consisted of leaders, division heads, and staff members of Bapenda as officially registered. Training materials included PDRD optimization, GRDP calculation methods, regional potential mapping, as well as the administration and management of technical guidance. The training applied a combination of interactive lectures, case studies, group discussions, and the development of a Follow-Up Action Plan (RTL). The results revealed significant improvement in participants’ comprehension of PDRD concepts, analytical skills in identifying tax potential, and the ability to design strategic plans for PAD optimization. This program is expected to serve as a starting point for strengthening regional revenue governance that is more effective, transparent, and data-driven.